Impact of the timing of hepatitis B virus identification and anti–hepatitis B virus therapy initiation on the risk of adverse liver outcomes for patients receiving cancer therapy. Issue 17 (18th May 2017) - Hwang, Jessica P.; Suarez‐Almazor, Maria E.; Cantor, Scott B.; Barbo, Andrea; Lin, Heather Y.; Ahmed, Sairah; Chavez‐MacGregor, Mariana; Donato‐Santana, Christian; Eng, Cathy; Ferrajoli, Alessandra; Fisch, Michael J.; McLaughlin, Peter; et al.
Abstract : BACKGROUND: Data on the incidence of adverse liver outcomes are limited for cancer patients with chronic (hepatitis B surface antigen [HBsAg]–positive/hepatitis B core antibody [anti‐HBc]–positive) or past (HBsAg‐negative/anti‐HBc–positive) hepatitis B virus (HBV) after chemotherapy. This study was aimed at determining the impact of test timing and anti‐HBV therapy on adverse liver outcomes in these patients. METHODS: Patients with solid or hematologic malignancies who received chemotherapy between 2004 and 2011 were retrospectively studied. HBV testing and anti‐HBV therapy were defined as early at the initiation of cancer therapy and as late after initiation. Outcomes included hepatitis flares, hepatic impairment, liver failure, and death. Time‐to‐event analysis was used to determine incidence, and multivariate hazard models were used to determine predictors of outcomes. RESULTS: There were 18, 688 study patients (80.4% with solid tumors). The prevalence of chronic HBV was 1.1% (52 of 4905), and the prevalence of past HBV was 7.1% (350 of 4905). Among patients with solid tumors, late identification of chronic HBV was associated with a higher risk of hepatitis flare (hazard ratio [HR], 4.02; 95% confidence interval [CI], 1.26‐12.86), hepatic impairment (HR, 8.48; 95% CI, 1.86‐38.66), liver failure (HR, 9.38; 95% CI, 1.50‐58.86), and death (HR, 3.90; 95% CI, 1.19‐12.83) in comparison with early identification. Among patients with hematologic malignancies and chronic HBV, the risk of death was 7.8 (95% CI, 1.73‐35.27) times higher for persons with late initiation of anti‐HBV therapy versus early initiation. Patients with late identification of chronic HBV had late or no anti‐HBV therapy. Chronic HBV predicted liver failure in patients with solid or hematologic malignancies, whereas male sex and late identification were predictors for patients with solid tumors. CONCLUSIONS: Early identification correlates with early anti‐HBV therapy and reduces the risk of liver failure and death in chronic HBV patients receiving chemotherapy. Cancer 2017;123:3367‐76 . © 2017 American Cancer Society . Abstract : The early identification of chronic hepatitis B virus infection reduces the risk of liver failure after chemotherapy among patients with solid tumors. Early anti–hepatitis B virus therapy is associated with a reduction in all‐cause mortality among hematologic patients with chronic hepatitis B virus infection.